Exploring the impact of mudra on respiratory function among Asthma Patients - S, Thamaraiselvi; Veda, Parthiban; Vidhya Shankari, S.; S, Ilamathi; Jayakandan, E.; Parthiban, Giridharan (Journal of Neonatal Surgery, 2025)
Background: Globally, the prevalence of asthma is rising, and drug therapy alone has yet to effectively manage it. We implemented nonpharmacological interventions like yoga with promising outcomes. This study aims to determine how mudra affects asthmatic patients' respiratory function. Aims and Objectives: The aim of the study was to find out the exploring the efficacy of 12 weeks of mudra practice on PEFR and BHT among asthma patients of yoga intervention group compared than the control group. Materials and Methods: 80 stable asthma patients between the ages of 30 - 45 were the subjects of this intervention. They were allocated into two groups at random, the control group (n=40) and the yoga practicing group (n=40). The yoga practicing group underwent mudra practice everyday morning and evening for 30 mins for 5 days a week for 12 weeks. Control group will not receive any yogic practices. PEFR and BHT tests were measured before and after 12 weeks using peak flow meter and stopwatch. Results: Statistically significant improvement (p < 0.05) was observed for PEFR and BHT in the yoga practicing group when compared with the control group. Conclusion: After 12 weeks of mudra practice, asthmatic patients' respiratory efficiency significantly improved.